A comparative bioequivalence study to evaluate the pharmacokinetic profile and safety of single-dose of dydrogesterone 10 mg tablets in healthy adult female volunteers - Sharma, Akhilesh D.; Chatterjee, Anindita; Vaddem, Radhakrishna (International Journal of Research in Medical Sciences, 2022)
Background: Dydrogesterone is a progesterone derivative. It is indicated in variety of disorders requiring progesterone administration. The basic aim of this bioequivalence (BE) study was to compare the pharmacokinetic profile of generic dydrogesterone 10 mg tablets (test product- Dydrosure) versus the innovator brand. Methods: This was a randomized, open-label, balanced, two-treatment, two-period, two-sequence, two-way crossover, single oral dose BE study conducted in healthy adult females under fasting conditions. A total of 28 subjects participated and 27 subjects completed both the study periods with 14 days washout in between. A total of 23 serial blood samples were collected starting from pre-dose to 72-hour post-dose. The primary pharmacokinetic parameters included peak plasma concentration (Cmax), area under the curve from zero to time t (AUC0-t) and zero to infinity (AUC0-inf); and 90% confidence intervals (CIs) of geometric least square mean (LSM) ratio of test product versus reference product were computed to evaluate the BE. The safety evaluation was based on reported adverse events (AEs) and laboratory parameters. Results: The 90% CIs of geometric LSM ratio of all primary pharmacokinetic parameters were within the range of 80 to 125%. The sequence, period and treatment did not have significant effect on the primary pharmacokinetic parameters. A single AE of dizziness was reported with the test product which was mild in intensity and transient in nature. Conclusions: Based on the statistical analysis of dydrogesterone, it is concluded that the test product (T): Dydrosure (dydrogesterone tablets IP 10 mg) manufactured by Alkem Laboratories Ltd., India is bioequivalent to the innovator’s brand, in terms of rate and extent of absorption under fasting conditions. The test product can be used interchangeably with the innovator’s brand.